Modern playhouses an architectural history of Britain's new theatres, 1945-1985 - Fair, Alistair (Oxford University Press, 2018)
A detailed study of the major programme of theatre-building in Britain between the 1950s and the 1980s, this book draws on a vast range of archival material to present the history of post-war theatre buildings as a history of ideas relating not only to performance but also to culture, citizenship, and the modern city
This edition previously issued in print: 2018. - Includes bibliographical references and index
Keywords: Geschichte 1945-1985; Theater architecture / Great Britain / History / 20th century; Theaters / Great Britain / History / 20th century; Architektur; Theaterbau; Großbritannien